Changes in Phenolic Compounds Profiles in Tea Extracts and the Composition of these Phenolic Compounds in Yogurt - Shori, Amal B.; Muniandy, Premalatha; Baba, Ahmad Salihin (Recent Patents on Food, Nutrition & Agriculture, 2021)
Background: Green, white, and black tea water extracts are rich in phenolic compounds. Objective: The changes in phenolic compound profiles of green, white, and black tea (GT, WT, & BT respectively) water extracts and their respective yogurt were investigated. Methods: Three types of yogurt with tea water extracts were prepared, and the phenolic compound profiles were analyzed using the liquid chromatography-mass spectrometry (LC-MS) method. Results: The present data found that flavonol glycosides such as kaempferol-3-rutinoside and quercetin-rhamnosylgalactoside or rutinoside were present in WT extract, whereas catechin derivatives such as gallocatechin (GC) and epigallocatechin (EGC) were present in GT extract. Moreover, theaflavin-3-O-gallate was observed in BT extract. Many of the catechin and its derivatives detected in the tea extracts were not identified in the tea yogurt samples. However, new phenolic compounds were present in GT-yogurt (i.e., kaempferol-3-rutinoside and quinic acid conjugate) but absent in GT extract. Conclusion: GT, WT, & BT extracts could be used to enriched-yogurt with phenolic compounds, which may have antioxidant properties.
Keywords: liquid chromatography-mass spectrometry (LC-MS)